1996
DOI: 10.1200/jco.1996.14.3.829
|View full text |Cite
|
Sign up to set email alerts
|

Combined preoperative chemotherapy and radiotherapy in patients with locally advanced esophageal cancer. Interim analysis of a phase II trial.

Abstract: This combined treatment modality is active in LAEC, with a PCR in 33% of the patients undergoing surgery. The results appear improved compared with those reported with surgery alone, by approximately doubling the 3-year survival rate. The high efficacy of preoperative chemoradiation warrants evaluation of the role of surgery in LAEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
92
1
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(99 citation statements)
references
References 15 publications
4
92
1
2
Order By: Relevance
“…However, cisplatin-based chemotherapy dose not sufficiently improve their overall survival, even when combined with additional irradiation (Stahl et al, 1996;Bosset et al, 1997). The results of these clinical trials suggest that it might be necessary to select the most effective therapy for each case in order to improve survival of patients with OSCC, especially advanced OSCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, cisplatin-based chemotherapy dose not sufficiently improve their overall survival, even when combined with additional irradiation (Stahl et al, 1996;Bosset et al, 1997). The results of these clinical trials suggest that it might be necessary to select the most effective therapy for each case in order to improve survival of patients with OSCC, especially advanced OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, nm23-H1 is likely to relate to responsiveness to cisplatin-based chemotherapy in patients with OSCC. Stahl et al (1996) have reported that overall 3-year survival rate was 33% in patients with T2-4 oesophageal carcinoma who underwent preoperative chemoradiotherapy and surgery. Likewise, we found that overall 3-year survival rate of 32 OSCC patients included in this study was 39.6%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study, together with the criteria for patient selection and study design, have been extensively described elsewhere (Stahl et al, 1996(Stahl et al, , 2005.…”
Section: Patientsmentioning
confidence: 99%
“…Recently, although neo-adjuvant chemoradiotherapy (CRT) followed by oesophagectomy has become widespread after several favourable pilot studies were reported (Poplin et al, 1996;Stahl et al, 1996;Ancona et al, 1997;Ide, 1997), contradictory data have also been published (Bosset et al, 1997;Tamin et al, 1998). A major problem in this context seems to be that a lower rate of cancerrelated deaths after combined treatment is counterbalanced by a higher rate of treatment-associated mortality.…”
mentioning
confidence: 99%